Artists and the Rothko Chapel 50 years of inspiration - Josenhans, Frauke V. 1979- (Moody Center for the Arts, 2021)
Artists and the Rothko Chapel celebrates the legacy of the Rothko Chapel in Houston and globally, highlighting how it has inspired artists since its founding in 1971. The catalogue reflects on the Chapel's past while looking toward its future, featuring recent work by four contemporary artists-Sam Gilliam, Sheila Hicks, Shirazeh Houshiary, and Byron Kim-as well as illustrating the 1975 exhibition Marden, Novros, Rothko: Painting in the Age of Actuality shown at Rice University. The volume includes interviews with Brice Marden and David Novros, statements from the artists about their work's relationship to the Chapel, and testimonies by local figures reflecting on questions of spirituality, identity, and equality. With new photography of the installations and of the recently restored Chapel, this vividly illustrated catalogue is a testament to the enduring impact of the non-denominational space Mark Rothko created
Impressum: Published in conjunction with the exhibition 'Artists and the Rothko Chapel: 50 Years of Inspiration', organized by the Moody Center for the Arts. Moody Center for the Arts, Rice, University, February 23-May 15, 2021
Keywords: Marden, Brice -- 1938-2023; Kim, Byron -- 1961-; Houshiary, Shirazeh -- 1955-; Gilliam, Sam -- Jr. -- 1933-2022; Novros, David -- 1941-; Hicks, Sheila -- 1934-; Geschichte 1971-2021; Rezeption; Kunst; Rothko Chapel -- Houston, Tex.; Ausstellungskatalog -- Moody Center for the Arts -- 23.02.2021-15.05.2021 -- Houston, Tex.; Bildband